2014
DOI: 10.1111/nph.12814
|View full text |Cite
|
Sign up to set email alerts
|

Live‐cell imaging of phosphatidic acid dynamics in pollen tubes visualized by Spo20p‐derived biosensor

Abstract: SummaryAlthough phosphatidic acid (PA) is structurally the simplest membrane phospholipid, it has been implicated in the regulation of many cellular events, including cytoskeletal dynamics, membrane trafficking and stress responses. Plant PA shows rapid turnover but the information about its spatio-temporal distribution in plant cells is missing. Here we demonstrate the use of a lipid biosensor that enables us to monitor PA dynamics in plant cells.The biosensor consists of a PA-binding domain of yeast SNARE Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 62 publications
7
95
0
Order By: Relevance
“…PtdOH biosensors have indicated that PtdOH is enriched at the apical and sub-apical plasma membranes in pollen tubes (Potocký et al, 2014;Simon et al, 2014). Interestingly, the same manipulations that affected the behaviour of a PtdOH biosensor in pollen tubes also affected the intracellular distribution of D6PK in root cells, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PtdOH biosensors have indicated that PtdOH is enriched at the apical and sub-apical plasma membranes in pollen tubes (Potocký et al, 2014;Simon et al, 2014). Interestingly, the same manipulations that affected the behaviour of a PtdOH biosensor in pollen tubes also affected the intracellular distribution of D6PK in root cells, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Black arrows, biosynthetic steps analysed in this study; grey arrows, biosynthetic steps that could not be selectively manipulated (Simon et al, 2016;Heilmann, 2009;Meijer and Munnik, 2003;Potocký et al, 2014 (Fig. S1).…”
Section: D6pk Plasma Membrane Association Is Phospholipid Dependentmentioning
confidence: 99%
See 2 more Smart Citations
“…The subcellular distribution of PA pools in plants is poorly characterized, although a new fluorescent reporter that shows great promise for future work indicates abundant PA at the plasma membrane of pollen tubes (Potocký et al, 2014). Furthermore, native PA binding proteins accumulate at the plasma membrane (Zhang et al, 2004), whereas in mammalian cells, PA is abundant in not only the plasma membrane, but also the ER, Golgi, and endosomal membranes (Rizzo et al, 2000;Baillie et al, 2002;Loewen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%